2000
DOI: 10.1016/s0304-3959(99)00187-6
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of back pain in the UK

Abstract: This paper reports the results of a 'cost-of-illness' study of the socio-economic costs of back pain in the UK. It estimates the direct health care cost of back pain in 1998 to be pound1632 million. Approximately 35% of this cost relates to services provided in the private sector and thus is most likely paid for directly by patients and their families. With respect to the distribution of cost across different providers, 37% relates to care provided by physiotherapists and allied specialists, 31% is incurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
820
0
18

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,272 publications
(852 citation statements)
references
References 17 publications
14
820
0
18
Order By: Relevance
“…Many people with chronic pain become disabled, resulting in a loss of identity, difficulty coping and a reduction in quality of life (Maniadakis & Gray, 2000). It is recommended that interventions that empower patients and encourage self-management should be utilised (Gifford, 1998;Frost et al, 2004;Turk & McCarberg, 2005).…”
Section: Background and Contextmentioning
confidence: 99%
“…Many people with chronic pain become disabled, resulting in a loss of identity, difficulty coping and a reduction in quality of life (Maniadakis & Gray, 2000). It is recommended that interventions that empower patients and encourage self-management should be utilised (Gifford, 1998;Frost et al, 2004;Turk & McCarberg, 2005).…”
Section: Background and Contextmentioning
confidence: 99%
“…Low back pain is a large socio-economic problem and is correlated with degeneration of the intervertebral disc (IVD) [1,2]. The IVD consists of the central nucleus pulposus (NP) and is surrounded by the ligamentous annulus fibrosus (AF).…”
Section: Introductionmentioning
confidence: 99%
“…It is recognised internationally that back problems are a major source of disability and can lead to lost labour force participation due to both retirement and absenteeism [1,9,10,27], with back problems keeping more Australians aged 45-64 years out of the workforce than any other condition [15]. Most of the studies that assess the indirect costs of back problems focus on the time lost to work absence as the main cost of back problems [1,5,9,12,13,28].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have indicated that the indirect costs of back pain are much larger than the direct medical and compensation costs [7,9]. Most of the studies undertaken in Australia and Europe have attributed most of these indirect costs to the work absenteeism caused by back problems [1,5,7,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation